Security Issues in Health Care (International Journal of Engineering and Computer Science, 2014)
Information systems in healthcare is   found to play a very crucial role in today’s scenario as more and more patient data is accumulated and it has become extremely crucial for correct and early diagnosis leading to early and effective treatment. Hence the issue of security of patient data is increasingly gaining popularity. Implementing security techniques in health centers is very much necessary to provide the controlled access, confidentiality and integrity to the patient   records. This paper presents a method using cryptographic means to improve trustworthiness of medical images, and healthcare information without compromising its quality to the end   user.  It also   analyzes the security measures that have been implemented to provide the controlled access in the current project using MD5 algorithm and identifying its limitations to provide probable solutions.